2024
DOI: 10.1097/ccm.0000000000006227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Treatments of Persistent Pulmonary Hypertension of the Newborn: A Systematic Review and Network Meta-Analysis

Qiang Fei,
Jiarong Pan,
Feizhou Zhang
et al.

Abstract: Objectives: Persistent pulmonary hypertension of the newborn (PPHN) is a life-threatening disease. Despite being considered the gold standard treatment scheme, inhaled nitric oxide (iNO) is not readily available in settings with limited resources. Therefore, in recent years, research on related drugs is being actively pursued. Herein, we aimed to use random-effects network meta-analysis to evaluate the efficacy and associated mortality of different PPHN therapies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…63 A recent systematic review and network meta-analysis has identified a median concentration of 10-20 parts per million iNO in conjunction with orally administered sildenafil at a dosage of 1-3 mg/kg/dose every 6-8 hours as the most effective treatment regimen for PHT. 64 The Congenital Diaphragmatic hernia Nitric Oxide versus Sildenafil (CoDiNOS) trial, an international randomized controlled trial comparing intravenous sildenafil against iNO for treating PHT in neonates with CDH, is currently in progress. The primary outcome of this trial is the absence of PHT on day 14 without the need for pulmonary vasodilator therapy and/or survival beyond the first 28 days of life.…”
Section: Sildenafilmentioning
confidence: 99%
“…63 A recent systematic review and network meta-analysis has identified a median concentration of 10-20 parts per million iNO in conjunction with orally administered sildenafil at a dosage of 1-3 mg/kg/dose every 6-8 hours as the most effective treatment regimen for PHT. 64 The Congenital Diaphragmatic hernia Nitric Oxide versus Sildenafil (CoDiNOS) trial, an international randomized controlled trial comparing intravenous sildenafil against iNO for treating PHT in neonates with CDH, is currently in progress. The primary outcome of this trial is the absence of PHT on day 14 without the need for pulmonary vasodilator therapy and/or survival beyond the first 28 days of life.…”
Section: Sildenafilmentioning
confidence: 99%